Deliberate practice on a virtual reality laparoscopic simulator enhances the quality of surgical technical skills - Crochet, Patrice; Aggarwal, Rajesh; Dubb, Sukhpreet Singh; Ziprin, Paul; Rajaretnam, Niroshini; Grantcharov, Teodor; Ericsson, K Anders; Darzi, Ara (Annals of surgery, 2011)
Virtual reality (VR) simulation provides unique training opportunities. This study evaluates whether the deliberate practice (DP) can be successfully applied to simulated laparoscopic cholecystectomy (LC) for enhancement of the quality of surgical skills. Twenty-six inexperienced surgeons underwent a training program for LC on a VR simulator. Trainees were randomly allocated to 1 of 2 specific protocols of 10 sessions comprising a total of 20 LCs. For each session, the control group performed 2 LCs separated by 30 minutes of occupational activities; the DP group were assigned 30 minutes of DP activities in between 2 LCs. Each participant then performed 2 LCs on a cadaveric porcine model. Quantitative parameters were recorded from the simulator and a motion tracking device; qualitative assessment utilized validated rating scales. Twenty-two subjects completed training. Learning curves on the VR simulator were significant for time taken and number of movements in both groups. The DP group was slower from the third LC (1373 vs. 872 seconds, P = 0.022) and utilized more movements from the seventh (942 vs. 701, P = 0.033). Global rating scores improved significantly in both groups over repeated LCs. The DP group revealed higher scores than control from tenth (19.5 vs. 14, P = 0.014) until the twentieth LC (22 vs. 16, P = 0.003). On the porcine model, the DP group also achieved higher global rating scores (25.5 vs. 19.5, P = 0.002). VR training improved dexterity for both groups, and led to transfer of skill onto a porcine LC model. The DP group achieved higher quality, and demonstrated superior transfer onto real tissues.